Porcine proliferative enteropathy: overview of disease dynamics and non-antibiotic alternatives for prevention and control strategies - Gómez-Osorio, Luis-Miguel; Penagos-Tabares, Felipe; Bosnjak-Neumuller, Jasna; Guedes, Roberto Mauricio Carvalho; Vasiljevic, Marko; Steiner, Tobias; McOrist, Steven (Frontiers in Veterinary Science, 2025)
Porcine proliferative enteropathy caused by the intracellular bacterium Lawsonia intracellularis remains an economically significant health concern in global pig farming. Clinical and subclinical forms of the disease commonly occur, resulting in substantial productivity losses due to effects on pig growth rate, feed efficiency, and mortality. Current management and control strategies rely primarily on effective vaccines and antibiotics. However, due to antimicrobial resistance being a global public health issue, there is a growing interest in and the need for research, development and large-scale implementation of novel and promising alternatives to antibiotics in animal production. This review integrates current research on novel prevention and management strategies, including current trends in phytotherapy (e.g., phytogenic feed additives), probiotics, prebiotics, immunomodulators, advanced vaccination protocols, and genetic resistance trends in swine. This review also discusses the implementation of biosecurity measures, cost-effectiveness, economic implications, and future perspectives of these strategies.